Health and economic effects of introducing single-dose or two-dose human papillomavirus vaccination in India - Partha Basu; Rengaswamy Sankaranarayanan; Ishu Kataria; Johannes Berkhof; Eric Lucas; Lopamudra Ray Saraswati; Iacopo Baussano; Richard Muwonge; Johannes A Bogaards; Tiago M de Carvalho; Irene Man; Damien Georges; et al. (BMJ Global Health, 2023)
Background Cervical cancer is a major public health problem in India, where access to prevention programmes is low. The WHO-Strategic Advisory Group of Experts recently updated their recommendation for human papillomavirus (HPV) vaccination to include a single-dose option in addition to the two-dose option, which could make HPV vaccination programmes easier to implement and more affordable.Methods We combined projections from a type-specific HPV transmission model and a cancer progression model to assess the health and economic effects of HPV vaccination at national and state level in India. The models used national and state-specific Indian demographic, epidemiological and cost data, and single-dose vaccine efficacy and immunogenicity data from the International Agency for Research on Cancer India vaccine trial with 10-year follow-up. We compared single-dose and two-dose HPV vaccination for a range of plausible scenarios regarding single-dose vaccine protection, coverage and catch-up. We used a healthcare sector payer perspective with a time horizon of 100 years.Results Under the base-case scenario of lifelong protection of single-dose vaccination in 10-year-old girls with 90% coverage, the discounted incremental cost-effectiveness ratio (ICER) of nationwide vaccination relative to no vaccination was US$406 (₹INR30 000) per DALY (disability-adjusted life-years) averted. This lay below an opportunity-cost-based threshold of 30% Indian gross domestic product per capita in each Indian state (state-specific ICER range: US$67–US$593 per DALY averted). The ICER of two-dose vaccination versus no vaccination vaccination was US$1404 (₹INR104 000). The ICER of two-dose vaccination versus single-dose vaccination, assuming lower initial efficacy and waning of single-dose vaccination, was at least US$2282 (₹INR169 000) per DALY averted.Conclusions Nationwide introduction of single-dose HPV vaccination at age 10 in India is highly likely to be cost-effective whereas extending the number of doses from one to two would have a less favourable profile.